Resolusi Sengketa Penarikan Sebagian Benda Wakaf oleh Ahli Waris Wakif Melalui Pendekatan Maqashid Al-Syari’ah Perspektif Hukum Positif - Mastri Imammusadin (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
Waqf land disputes are a widespread phenomenon in society. It is not uncommon for a lawsuit to be filed by the wakif himself, or by the wakif's heirs, so that the purpose of waqf as worship with social functions is often constrained. Not to mention the conflicts that can never be resolved because of the feeling of